The socioeconomic benefits of the 6 GHz band: Considering licensed and unlicensed options - Kalvin Bahia; Pau Castells (International Telecommunications Society (ITS), 2022)
Considerations on the optimal approach for managing spectrum are currently at the forefront of the debate around the 5925-7125 MHz frequency range (the '6 GHz band'), as Governments decide how best to manage this spectrum over the coming decades. We apply a cost-benefit analysis, using a supply and demand framework, in 24 countries to identify the policies that will maximise the social and economic value of this spectrum. We find that the optimal assignment policy primarily depends the expected adoption of 5G and fixed fibre/cable broadband services in each market, the speeds that fixed broadband can offer consumers, the existing and future spectrum availability for licensed and unlicensed use, and usage of high bands by 5G and Wi-Fi. In most countries, allocating the full 6 GHz band for licensed mobile use will drive the greatest benefit. Allocating the lower 6 GHz band for licence-exempt use and the upper 6 GHz band for licensed mobile use could drive the greatest economic benefit in countries with very high fibre and cable broadband adoption and if fixed broadband speeds can reach up to 5-10 Gbps. Allocating the full 6 GHz band for licence-exempt use will not be the most beneficial option in any of the considered analyses.
Keywords: D61; L51; L96; 330